Nightshade - Connelly, Michael, 1956- (New York : Little Brown and Company, 2025)
Introducing Detective Stilwell: a cop relentlessly following his mission in the seemingly idyllic setting of Catalina Island. Los Angeles County Sheriff's Detective Stilwell has been "exiled" to a low-key post policing rustic Catalina Island, after department politics drove him off a homicide desk on the mainland. But while following up the usual drunk-and-disorderlies and petty thefts that come with his new territory, Detective Stilwell gets a report of a body found weighed down at the bottom of the harbor--a Jane Doe identifiable at first only by a streak of purple dye in her hair. At the same time, a report of poaching on a protected reserve turns into a case fraught with violence and danger as Stilwell digs into the shady past of an island bigwig. Crossing all lines of protocol and jurisdiction, Stilwell doggedly works both cases. Though hampered by an old beef with an ex-colleague determined to thwart him at every turn, he is convinced he is the only one who can bring justice to the woman known as "Nightshade." Soon, his investigation uncovers closely guarded secrets and a dark heart to the serene island that was meant to be his escape from the evils of the big city. Propulsive and atmospheric, Nightshade launches a brand new character into the Connelly universe, and proves without question that Michael Connelly is "the undisputed master of the modern crime novel" Provided by the publisher.
Keywords: Detectives -- Fiction; Police -- California -- Los Angeles -- Fiction; Murder -- Investigation -- Fiction; Poaching -- Fiction; Islands -- Fiction; Secrecy -- Fiction; Corruption -- Fiction; Los Angeles (Calif.) -- Fiction; Santa Catalina Island (Calif.) -- Fiction; Detective and mystery fiction; Suspense fiction; Thrillers (Fiction).